SLG controls grain size and leaf angle by modulating brassinosteroid homeostasis in rice - Feng, Zhiming (J Exp Bot, 2016)
Grain size and leaf angle are two important traits determining grain yield in rice. However, the mechanisms regulating the two traits remain largely unknown. Here, we characterized a rice gain-of-function mutant, slender grain Dominant (slg-D), which exhibited longer and narrower grains and larger leaf angles, similar to plants with elevated brassinosteroid (BR) levels or strengthened BR signaling. The increased cell length is responsible for the mutant phenotypes in slg-D. We demonstrated that the phenotype of slg-D is caused by enhanced expression of SLG, a BAHD acyltransferase-like protein gene. SLG is preferentially expressed in young panicles and lamina joints, implying its role in controlling cell growth in those two tissues. slg-D was restored to wild type by treatment with brassinazole, an inhibitor of BR biosynthesis. Overexpression of SLG in d11-2 (deficient in BR synthesis) and d61-1 (deficient in BR signaling) did not change the existing phenotypes. The slg-D plants had elevated BR contents and, accordingly, expression of BR-related genes was changed in a manner similar to BR treatment. Moreover, SLG RNAi plants displayed mild BR-deficient phenotypes including shorter grains, smaller leaf angles, and compact semi-dwarf plant types. The in vitro biochemical assays and transgenic approaches collectively demonstrated that SLG functions as homomers. Taken together, we conclude that SLG is an important regulator in BR homeostasis and that manipulation of SLG expression to an optimal level may provide a way to develop an ideal plant type.